The Effect of Myopia and Loss Aversion on Risk Taking: An Experimental Test - Thaler, R. H.; Tversky, A.; Kahneman, D.; Schwartz, A. (Quarterly Journal of Economics, 1997)
Myopic loss aversion is the combination of a greater sensitivity to losses than to gains and a tendency to evaluate outcomes frequently. Two implications of myopic loss aversion are tested experimentally. 1. Investors who display myopic loss aversion will be more willing to accept risks if they evaluate their investments less often. 2. If all payoffs are increased enough to eliminate losses, investors will accept more risk. In a task in which investors learn from experience, both predictions are supported. The investors who got the most frequent feedback (and thus the most information) took the least risk and earned the least money.